Stress Analysis of Bioceramic Coated Orthopaedic Implants. (2018) - Meenachi, P.; Subashini, R.; Suresh Kumar, S.
Abstract: In biomedical applications, bioceramics are commonly used to modify the surface properties of the metals in exploitation as orthopedic implants for humans. The diseases such as osteoporosis, osteoarthritis, bone tumour and trauma are the reasons for joint replacements in population over 50 years of age in developed countries. The Total Hip Replacement (THR) is an excellent alternative for patients suffering from joint failure caused by osteoarthritis. The historical failure of artificial implant restorative procedure has been due to the wear of components with subsequent bone resorption and aseptic loosening that limits the lifespan of implants. Multiple different materials made from stainless steel, cobalt, chromium, titanium, and tantalum have been tested throughout history as replacements for bone. Even through the metallic materials have the required mechanical properties, the hydroxyapatite coatings which provide an osteophilic surface for bone to bond to, anchoring the implant and transferring load to the skeleton, helping to combat bone atrophy. In the present work, a finite element model of hip implant has been designed with standard parameters. The stress distribution and deformation behavior of the designed hip implant was analyzed under static conditions for different material properties (316L Stainless steel, Titanium, and Cobalt-Chromium) with and without considering bioactive ceramic coating hydroxyapatite (HAP). It was observed that, the stress distribution for the coated hip implant showed 20 -30% reduction in 316L Stainless steel, 30% in Titanium alloy and 20% in cobalt chromium alloy. Among them, Cobalt-Chromium alloy provides better reduction in stress distribution and deformation compared to other materials. Thus one can conclude that, a bioactive coating has tremendous potential for improving bone integration of wide range of dental and orthopaedic implants.